QUBIC VII: The feedhorn-switch system of the technological demonstrator. Issue 4 (1st April 2022) - ,; Cavaliere, F.; Mennella, A.; Zannoni, M.; Battaglia, P.; Battistelli, E.S.; de Bernardis, P.; Burke, D.; D'Alessandro, G.; De Petris, M.; Franceschet, C.; Grandsire, L.; et al.
Abstract: We present the design, manufacturing and performance of the horn-switch system developed for the technological demonstrator of QUBIC (the Q&U Bolometric Interferometer for Cosmology). This system consists of 64 back-to-back dual-band (150 GHz and 220 GHz) corrugated feed-horns interposed with mechanical switches used to select desired baselines during the instrument self-calibration. We manufactured the horns in aluminum platelets milled by photo-chemical etching and mechanically tightened with screws. The switches are based on steel blades that open and close the waveguide between the back-to-back horns and are operated by miniaturized electromagnets. The measured electromagnetic performance of the feedhorns agrees with simulations. In particular we obtained a return loss around –20 dB up to 230 GHz and beam patterns in agreement with single-mode simulations down to –30 dB. The switches for this prototype were designed and built for the 150 GHz band. In this frequency range we find return and insertion losses consistent with expectations (< –25 dB and ∼ –0.1 dB, respectively) and an isolation larger than 70 dB. In this paper we also show the current development status of the feedhorn-switch system for the QUBIC full instrument, based on an array of 400 horn-switch assemblies.